Cognitive behavior therapy for chronic fatigue syndrome: efficacy and implications. - Sharpe, M (1998)
Cognitive behavior therapy (CBT) is a form of non-pharmacologic treatment. It is based on a model of chronic fatigue syndrome (CFS) that hypothesizes that certain cognitions and behavior may perpetuate symptoms and disability--that is, act as obstacles to recovery. Treatment emphasizes self-help and aims to help the patient to recover by changing these unhelpful cognitions and behavior. There is now good evidence from 2 independent randomized clinical trials to support the efficacy of CBT in patients with CFS. The treatment effect is substantial, although few patients are cured. The urgent clinical need is to make this form of treatment available to patients with CFS. One approach is to incorporate the principles of CBT into routine clinical practice. The preliminary evaluation of these simpler forms of CBT are promising, although the results of controlled trials are awaited. At present, intensive individual CBT administered by a skilled therapist remains the treatment of choice for patients with CFS.